Performance and Return to Sports After Meniscectomy in Professional Baseball Players. Issue 4 (March 2022) - Erickson, Brandon J.; Chalmers, Peter N.; D'Angelo, John; Ma, Kevin; Rowe, Dana; Ciccotti, Michael G.; Dugas, Jeffrey R.
Background: Meniscal injuries are common in athletes across many sports. How professional baseball players respond to partial meniscectomy is not well documented. Purpose/Hypothesis: The purpose was to determine the performance and return-to-sports (RTS) rate in professional baseball players after arthroscopic partial knee meniscectomy and compare the results of partial medial meniscectomy versus partial lateral meniscectomy. The hypothesis was that there would be a high RTS rate in professional baseball players after partial meniscectomy with no difference in the RTS rate or timing of RTS between players who underwent partial medial meniscectomy versus partial lateral meniscectomy. Study Design: Cohort study; Level of evidence, 3. Methods: All professional baseball players who underwent arthroscopic partial meniscectomy between 2010 and 2017 were identified using the Major League Baseball Health and Injury Tracking System database. Demographic and performance data (before and after injury) for each player were recorded. The RTS rate and timing of RTS were then compared between players who underwent partial medial meniscectomy versus partial lateral meniscectomy. Results: A total of 168 knees (168 players) underwent arthroscopic partial meniscectomy (mean age, 25 ± 5 years; 46% medial meniscectomy, 45% lateral meniscectomy, and 9% both medial and lateral meniscectomy). The most common mechanism of injury was fielding in the infield on natural grass. Injuries were spread evenly across positions: 18% catchers, 24% infielders, 20% outfielders, and 38% pitchers. The overall RTS rate was 80% (76% returned to the same or a higher level, and 4% returned to a lower level). For performance, pitchers saw significant decreases in usage but significant improvements in performance using the advanced statistics of fielding independent pitching ( P < .001) and wins above replacement ( P = .011). Hitters saw significant decreases in usage but increases in efficiency as seen by improvements in wins above replacement ( P = .003). Of the 79 athletes who returned during the same season, the median time to return to play was 42 days. Conclusion: The RTS rate after meniscectomy in professional baseball players was 80%. Player efficiency improved after surgery in pitchers and position players. No difference in the RTS rate or timing of RTS existed between players who underwent partial medial meniscectomy versus partial lateral meniscectomy.